Liangzhu’s Story of Stone - Ji, Xiang. author. aut Link
X, 99 p. 88 illus., 84 illus. in color.
Keywords: This book explains how the walls of Liangzhu City were made from bedding stones and mud, with the total area of bedding stones covering roughly 290,000 square meters. Based on ongoing research and studies, the book tells the story of how these stones were collected from the surrounding mountains and how their mining and use required massive manpower and material resources, indicating what a tremendous undertaking the construction of Liangzhu City was. The book also shares insights into the process of discovering and researching the city wall, as well as the stoneware at the Liangzhu historical site complex.